2010
DOI: 10.4012/dmj.2009-141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PMMA filler particles addition on the physical properties of resin composite

Abstract: The aim of this study was to evaluate the effect of additional polymethyl methacrylate (PMMA) fillers on the physical properties of experimental resin composites. PMMA particles (d=30 µm) were added to an experimental methacrylate-based resin composite in five concentrations of 0, 2.0, 4.8, 9.1, and 23.1 wt%. Properties such as contact angle, water sorption and compressive strength were measured and the fractured specimens were observed with a scanning electron microscope. The results showed that a small amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The anti-adherence and bactericidal properties of nano silver-containing composites against mutans streptococci are reported in some previous studies. 5,6,11,16,17 Although nano silver particles might be useful as an antibacterial agent incorporated into dental composites, this metal influences the color of the esthetic restorative materials and reduces water contact angles of the heavily filled composite resins. Therefore, addition of silver nano particles into composite resin restorations may not be clinically advantageous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-adherence and bactericidal properties of nano silver-containing composites against mutans streptococci are reported in some previous studies. 5,6,11,16,17 Although nano silver particles might be useful as an antibacterial agent incorporated into dental composites, this metal influences the color of the esthetic restorative materials and reduces water contact angles of the heavily filled composite resins. Therefore, addition of silver nano particles into composite resin restorations may not be clinically advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Silorane-based composites are claimed to have a higher contact angle and a lower amount of plaque adhesion compared to methacrylate-based composites. 7 In operative dentistry, secondary caries is the main reason for restoration replacement.…”
Section: Introductionmentioning
confidence: 99%
“…Since there have been no significant advances in improving the properties of polymer matrix materials, recent improvements in resin composite properties are due primarily to advances in filler technology 15) . Generally, particles (random orientation), whiskers (single or multi-layer) and fibers (long or short fibers in various orientations) have been used to reinforce resin composite materials [16][17][18][19] . Fiber-reinforced resin composites have been shown to possess a suitable flexural strength and elastic modulus to function successfully in oral cavities 20) .…”
Section: Introductionmentioning
confidence: 99%
“…Tjisumoto et al, on the other hand reported that a thin layer of contaminant remains on the zirconia ceramic surface after exposure to saliva, significantly impeding bonding of the resin cement and reducing surface free energy of the ceramics [19]. Likewise, Kondo et al investigated surface properties of PMMA-containing resin composites and reported that contact angle of the experimental materials tended to increase with incorporation of PMMA fillers in the resin composite, thus increasing surface hydrophobicity of the material [29]. According to published literature [19,[28][29][30], materials with contact angle above 65° are considered highly hydrophobic.…”
Section: Discussionmentioning
confidence: 99%